2022
DOI: 10.1038/s41467-022-35477-x
|View full text |Cite
|
Sign up to set email alerts
|

Torsional periodic lattice distortions and diffraction of twisted 2D materials

Abstract: Twisted 2D materials form complex moiré structures that spontaneously reduce symmetry through picoscale deformation within a mesoscale lattice. We show twisted 2D materials contain a torsional displacement field comprised of three transverse periodic lattice distortions (PLD). The torsional PLD amplitude provides a single order parameter that concisely describes the structural complexity of twisted bilayer moirés. Moreover, the structure and amplitude of a torsional periodic lattice distortion is quantifiable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
(70 reference statements)
0
17
0
Order By: Relevance
“…However, Rosenberger et al reported that the heterostructure of MoSe 2 and WSe 2 with a twist angle of 3° showed no reconstruction . On the other hand, there is a recent report of observation of torsional periodic lattice distortions, similar to that observed in MoS 2 /WSe 2 , in MoSe 2 /WSe 2 TBL with a twist angle of 5°. This suggests that such periodic lattice distortions can provide the in-plane restoring force necessary to sustain the LS modes.…”
Section: Resultsmentioning
confidence: 97%
“…However, Rosenberger et al reported that the heterostructure of MoSe 2 and WSe 2 with a twist angle of 3° showed no reconstruction . On the other hand, there is a recent report of observation of torsional periodic lattice distortions, similar to that observed in MoS 2 /WSe 2 , in MoSe 2 /WSe 2 TBL with a twist angle of 5°. This suggests that such periodic lattice distortions can provide the in-plane restoring force necessary to sustain the LS modes.…”
Section: Resultsmentioning
confidence: 97%
“…Though above θ m , the shape of the soliton walls is geometrically less regular in comparison as shown in Figure 4 b due to softening of the domain boundaries. 29 …”
Section: Resultsmentioning
confidence: 99%
“…Though above θ m , the shape of the soliton walls is geometrically less regular in comparison as shown in Figure 4b due to softening of the domain boundaries. 29 For small twist angle TBGs at or below θ m , the energetically unfavorable AA domains shrink drastically upon reconstruction, which translates to a large change in their area fraction. For example, the area fraction of AA regions in the θ m = 1.08°s tructure shows a dramatic reduction of 76% upon relaxation (Figure 4f).…”
Section: Iiic1 Comparison Of Reconstructed Structures Below and Beyon...mentioning
confidence: 99%
See 1 more Smart Citation
“…The relative twisted angle between layers, in 2D materials such as TBLG 7,8 , has become an undeniable phenomenon and a new eld. In this way, magic angle value provided a novel knob for tuning superconducting properties 1 and many-body effects 2,9,10 .…”
Section: Introductionmentioning
confidence: 99%